Educação e humanização de bebês e de crianças pequenas conceitos e práticas pedagógicas - Kohle, Érika Christina (Editora Oficina Universitária, 2020)
This book was born from the development of the discipline Pedagogical Implications of Historical-Cultural Theory and Early Childhood Education of the Graduate Program in Education at Unesp, Campus de Marília, SP. It presents some reflections on aspects of human development in early childhood, considering the experiences lived by children since their birth that shape their personality and intelligence - which has been more recently proven by neuroscience. It reveals some ways to better promote human development in childhood, which involve a new way of organizing space - with a variety of materials: from books to natural materials that can be used in multiple ways by children, that are accessible to their hands, that are organized in a perceptible way with children, that present culture in its most elaborate forms (VYGOTSKY, 2018) without underestimating the possibility of children educating their sensitivity either for science or for art. A new school culture also involves new forms of organization and time management that allow children free time to choose activities, times of diversified activity in which there is the possibility of choosing between some activities proposed by the teacher, in addition to activities presented by the teacher with the purpose of expanding what children already know. These new forms of organization and time management respect children's times, considering that they are different from adults' times. For this reason, the forms of anticipation of schooling and the abbreviation of childhood that have been imposed on Early Childhood Education schools with the approval of many families do not fit. This new school culture also involves new forms of relationship between adults and children, it requires deepening the reception and listening to the desires, interests and needs of children as a method of teaching work: horizontal relationships that guarantee the participation of children and cooperation between adults and children in the organization of life at school; communication relationships between adults and children in accessing knowledge, culture. And all this will lead to a new quality of the activities proposed and carried out at school - in the sense that the Historical-Cultural Theory gives to the term activity: involving the child with the body, thought and emotion in the situations experienced. This set of reflections guides the thinking and acting of teachers towards respect for times and the ways babies and children live their adventure of knowing the world and expanding their experiences to contemplate human development for all children in their maximum possibilities. The historical-cultural approach supports us for this, we must venture to make this school a fact.